A ERA DA DELEGAÇÃO DAS RESPONSABILIDADES - Moura, João Carlos da Cunha (2014)
The following dissertation seeks understand about the modern concepts of subjectivity and juridical thought, as well their institutional reflect. Investigate the relationship between I and other as driven and universalized conducts. After this theoretical definition, based upon the dialectical study on Jürgen Habermas e Michel Foucault, the work searches differentiate public and political in the democratic and constitutional context, exploring the institutional formation of State as enterprise of Law and whose interests are elevated in the construction of the later. From the logical of separation of powers, analyses the space of political domain. Finally, it intends to question about delegations of responsibilities to the Public Power: a society that inserted itself in an age of delegations of responsibilities of private matters which charges to the scope of Public Power taking actions about responsibilities and decisions of individual imprint, whose direction is given by devices (laws, sentences etc.) that creates a legitimate discourse about the theme which wants to debate, setting, at the end of a chain of relations of power, socials and normative, the Judiciary.